2020
DOI: 10.1111/acem.14177
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Computed Tomography Scan Utilization for Pediatric Minor Head Injury in the Emergency Department: A Quality Improvement Initiative

Abstract: Background The validated Pediatric Emergency Care Applied Research Network (PECARN) prediction rules are meant to aid clinicians in safely reducing unwarranted imaging in children with minor head injuries (MHI). Even so, computed tomography (CT) scan utilization remains high, especially in intermediate‐risk (per PECARN) MHI patients. The primary objective of this quality improvement initiative was to reduce CT utilization rates in the intermediate‐risk MHI patients. Methods This project was conducted in a Leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The most commonly targeted patient diagnosis was bronchiolitis [ 48 , 90 , 104 , 112 , 119 ], pulmonary embolism [ 49 , 58 , 60 , 82 , 100 , 102 , 121 , 122 , 125 ], and head injuries [ 67 , 70 , 77 , 79 , 87 , 94 , 101 , 123 , 126 , 127 ]. In studies targeting these complaints, a reduction in use of low-value imaging were reported in 78–80% of the studies, while imaging in lower back pain [ 38 , 45 , 51 , 53 , 54 , 65 , 68 , 71 , 75 , 89 , 115 , 118 ] were reduced in 58% of studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly targeted patient diagnosis was bronchiolitis [ 48 , 90 , 104 , 112 , 119 ], pulmonary embolism [ 49 , 58 , 60 , 82 , 100 , 102 , 121 , 122 , 125 ], and head injuries [ 67 , 70 , 77 , 79 , 87 , 94 , 101 , 123 , 126 , 127 ]. In studies targeting these complaints, a reduction in use of low-value imaging were reported in 78–80% of the studies, while imaging in lower back pain [ 38 , 45 , 51 , 53 , 54 , 65 , 68 , 71 , 75 , 89 , 115 , 118 ] were reduced in 58% of studies.…”
Section: Resultsmentioning
confidence: 99%
“…Implementation of multi-component interventions (2 or more components in combination) reportedly reduced the use of low-value imaging among 94% of the included studies [ 40 44 , 47 , 48 , 51 , 53 , 56 , 59 , 63 , 72 , 78 , 79 , 81 , 83 , 86 , 87 , 94 , 101 , 104 , 105 , 111 , 115 , 116 , 118 , 120 , 122 , 123 , 126 , 128 ]. Multi-component interventions were found to be more effective when education was one of the components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These may result in knowledge gaps with regard to best pediatric practices, partly explaining the increased use of radiographs at these institutions. 45,46,48,59 Radiograph use was highest in hospitals with higher pediatric volumes. This finding differs from the large body of "volumeoutcome" literature suggesting that higher volumes lead to better adherence to guidelines and better outcomes, for both pediatric and adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of specific skills or exposure to ED-specific clinical practice guidelines in PEM training may also explain some of the variation. 45,46,48 No studies have specifically evaluated the underlying causes of these differences in low-value radiograph use. Our findings suggest that ED setting and physician specialty training warrant further exploration, perhaps through qualitative studies, to inform future interventions.…”
Section: Discussionmentioning
confidence: 99%